2014
DOI: 10.1021/jp5082438
|View full text |Cite
|
Sign up to set email alerts
|

DFT Study of the Reaction of a Two-Coordinate Iron(II) Dialkyl Complex with Molecular Oxygen

Abstract: DFT studies are reported of a monomeric iron dialkyl for which oxygen atom insertion into metal-methyl bonds occurs with O2: FeMe2 + O2 → Fe(OMe)2. Computation of the reaction coordinate implicates the intermediacy of Fe(III)-peroxo, Fe(VI)-dioxo, and Fe(IV)-oxo intermediates, connected by O2 oxidative addition and two methyl migration steps. Analysis of the reaction of O2 with d(6)-Fe(Me)2 indicates that oxy-insertion for this iron complex occurs with lower free energy barriers than competing homolytic/radica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 45 publications
2
8
0
Order By: Relevance
“…Neidig and co‐workers had also noted the high sensitivity of Me 12 Fe 8 − toward air. Although the structure of [Fe 8 ,Me 12 ,O 2 ] − is unknown, the incorporation of highly electronegative oxygen atoms into the cluster is likely to stabilize its negative charge. Thus, [Fe 8 ,Me 12 ,O 2 ] − presumably has a particularly high ESI activity, which implies that even very small amounts of this species should give rise to a notable signal intensity.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Neidig and co‐workers had also noted the high sensitivity of Me 12 Fe 8 − toward air. Although the structure of [Fe 8 ,Me 12 ,O 2 ] − is unknown, the incorporation of highly electronegative oxygen atoms into the cluster is likely to stabilize its negative charge. Thus, [Fe 8 ,Me 12 ,O 2 ] − presumably has a particularly high ESI activity, which implies that even very small amounts of this species should give rise to a notable signal intensity.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the clusteri ons Me 13 Fe 8 À and [Fe 8 ,Me 12 ,O 2 ] À (Supporting Information, Figure S2) were detectedi nc onsiderably lower signal intensities. The observation of the former indicates that Me 12 Fe 8 À is not the only cluster ion produced from transmetalation under typical reaction conditions of ironcatalyzed cross-coupling.T he oxygen-containing species [Fe 8 ,Me 12 ,O 2 ] À presumably resulted from the reactiono f Me 12 Fe 8 À with traces of dioxygen present in the sample solution or the mass spectrometer.N eidig and co-workers had also noted the high sensitivity of Me 12 Fe 8 À towarda ir.A lthough the structure of [Fe 8 ,Me 12 ,O 2 ] À is unknown, [12] the incorporation of highly electronegative oxygen atoms into the clusteri sl ikely to stabilize its negative charge. Thus, [Fe 8 ,Me 12 ,O 2 ] À presumably has ap articularly high ESI activity,w hich implies that even very small amountso ft his species should give rise to an otable signal intensity.…”
Section: Reaction Of Fe(acac) 3 With Memgxmentioning
confidence: 99%
See 2 more Smart Citations
“…For iron-specific systems, Power has shown that Fe-aryl complexes exhibit formal O=O scission and O-atom insertion into M-Caryl bonds. 38,39 In an extensive DFT study on the related O2 reaction with the twocoordinate compound FeMe2, 40 Cundari reported that the O-atom insertion is calculated to proceed via initial formation of open-shell Fe III -(O2 -) species and eventual generation of dioxo intermediates (as seen in Cr oxidation chemistry reported by Theopold) 41 prior to O-atom insertion into the Fe-C bonds. Additionally, Chirik has shown that ferrous dialkyls are susceptible to Fe-C homolysis upon addition of π-acidic redox-active ligands, 42 suggesting that coordination of O2 could lead to the generation of free alkyl radicals.…”
mentioning
confidence: 99%